Increasing STEM career interest: The role of out-of-school time STEM programs designed for underrepresented minorities - Maria Dresser; Kelly Miller; Gerhard Sonnert; Philip Sadler (PLoS ONE, 2025)
The creation of a large and diverse STEM workforce is a national imperative in the U.S. Despite significant efforts to improve equitable STEM educational and hiring practices, disparate employment in STEM fields across racial and ethnic demographics persists. Educational researchers and practitioners have increasingly focused on out-of-school time STEM programs as a potential avenue for boosting high school students’ interest in pursuing STEM careers. However, many studies on the efficacy of such programs rely on data from single programs with small sample sizes. The present work uses our nationally representative sample of 14,176 U.S. college students to investigate the relationship between out-of-school time STEM program attendance and students’ reported STEM career interests. Our analysis shows that students who, during their high school years, attended an out-of-school time STEM program designed specifically for underrepresented minority students had 2.4 times the odds of reporting an interest in a STEM career at the end of high school, compared to those who did not attend any out-of-school time STEM program ( p < 0 . 001 ) . By contrast, students who attended a general population STEM program (not specifically designed for underrepresented minority students) had only 1.3 times the odds of expressing an interest in a STEM career at the end of high school, compared to those who did not attend any out-of-school time STEM program ( p < 0 . 001 ) . Additionally, those who attended an underrepresented minority STEM program had 1.9 times the odds of aspiring to a STEM career, compared to those who attended a general population program ( p < 0 . 001 ) . This is the first study to use nationally representative data to compare underrepresented minority focused and general out-of-school time STEM programs. Given these promising results, this work encourages further development and funding of out-of-school time STEM programs designed for underrepresented minorities to foster a diverse and equitable STEM workforce.